Plano Nacional de Educação (2014-2024): análise da educação infantil no município de Passos/MG - Marques, Simone Carvalho Silva (2023)
This work was dedicated to analyzing the implementation and monitoring of Goal 1 of the National Education Plan (2014-2024), in the municipality of Passos, MG. Current norms and laws were analyzed and documentary research was carried out based on documents produced by the municipality's Education Department and the PME-Pas sos/MG Monitoring Committee. Budgetary and statistical data relating to enrollments were researched and analyzed, as well as the application of resources made available on the website of the National Education Development Fund and Integrated Planning System. Inconsistencies were found in the monitoring aimed at meeting the PNE goals, which impacted the generation of data and consequently the verification of the effec tiveness of the measures adopted. It is also important to highlight the impact of the Covid-19 Pandemic, which occurred during the plan's validity period, on achieving the goals. The difficulties encountered by the municipality in organizing itself to manage the execution of the Plan and meet the stipulated goals thus became clear. Such diffi culties are due both to the way monitoring was carried out and to the scarcity of re sources for such purposes. This situation demonstrates how public educational poli cies still lack attention and commitment at different levels of the federation.